Crystalline defect analysis in epitaxial Si0.7Ge0.3 layer using site-specific ECCI-STEM. (November 2021) - Han, Han; Strakos, Libor; Hantschel, Thomas; Porret, Clement; Vystavel, Tomas; Loo, Roger; Caymax, Matty
Highlights: A unique combination of ECCI and in-situ-subsequent-STEM-in-SEM has been carried out in one dual-beam SEM/FIB system. The method enables the site-specific 2.5D defect analysis, significantly improving the analysis efficiency and throughput. This method is powerful to find out and distinguish the nature of line-featured defects as demonstrated using Si0.7 Ge0.3 . The ECCI information depth has been determined using stacking faults from ECCI and confirmed by cross-sectional STEM. Abstract: Electron channeling contrast imaging (ECCI) is a powerful technique to characterize the structural defects present in a sample and to obtain relevant statistics about their density. Using ECCI, such defects can only be properly visualized, if the information depth is larger than the depth at which defects reside. Furthermore, a systematic correlation of the features observed by ECCI with the defect nature, confirmed by a complementary technique, is required for defect analysis. Therefore, we present in this paper a site-specific ECCI-scanning transmission electron microscopy (STEM) inspection. Its value is illustrated by the application to a partially relaxed epitaxial Si0.7 Ge0.3 on a Si substrate. All experiments including the acquisition of ECCI micrographs, the carbon marking and STEM specimen preparation by focused ion beam, and the in-situ-subsequent-STEM-in-scanning electron microscopy (SEM) characterization were executed in one SEM/FIB-based system, thus significantly improving the analysis efficiency. The ECCI information depth in Si0.7 Ge0.3 has been determined through measuring stacking fault widths using different beam energies. ECCI is further utilized to localize the defects for STEM sample preparation and in-situ-subsequent-STEM-in-SEM investigation. This method provides a correlative 2.5D defect analysis from both the surface and cross-section. Using these techniques, the nature of different line-featured defects in epilayers can be classified, as illustrated by our study on Si0.7 Ge0.3, which helps to better understand the formation of those detrimental defects.